Science wizardry for kids - Kenda, Margaret; Williams, Phyllis S. (Hauppauge, N.Y. : Barron$1 (Bs,s, 1992)
Includes over two hundred projects that enable young scientists to make secret formulas, blow bubbles of all sizes and colors, grow smart plants, make predictions, and more.
Includes index.
Keywords: Science -- Experiments -- Juvenile literature; Scientific recreations -- Juvenile literature; Scientific recreations; Science -- Experiments